Penerapan Layanan Konseling Kelompok Teknik Self Management untuk Mengurangi Kecanduan Game Online Mobile Legends terhadap Siswa Kelas XII F-6 di SMA Negeri 2 Kudus - Putri Retnaningsih; Agung Slamet Kusmanto; Sumarwiyah (BIMBINGAN DAN KONSELING BANYUWANGI, 2025)
Online game addiction can be defined as an activity that involves excessive online gaming. So, it can make students ignore their duties, namely learning and doing assignments because they are busy playing online games. The objectives of this study are: 1. To determine the application of group counseling services of self management techniques to reduce addiction to game online Mobile Legends in class XII F-6 SMA Negeri 2 Kudus students. 2. To determine the group counseling services of self-management techniques are effective in reducing addiction to game online Mobile Legends in students of class XII F-6 SMA Negeri 2 Kudus. This research uses a type of quantitative research using the Quasi-Experimental Design (Quasi-Experiment) method with One-group Pretest-Posttest Design. The results of this study indicate that before group counseling services with self-management techniques (pre-test) students had a high level of addiction to mobile legends online games with an average of 98.5 and after group counseling services with self management techniques (post-test) had an average of 63.5 with a difference of 35.5% which means a decrease. The results of statistical data interpretation in the Wilcoxon test obtained a significance of 0.028. The value of Asymp. Sig. (2-tailed) of 0.028 <0.05 so that the hypothesis is accepted. The contribution of this research for counseling is to add insight and knowledge that self-management techniques are one of the right methods in solving problems regarding online game addiction